Dynamic epigenetic states of maize centromeres - Liu, Yalin; Su, Handong; Zhang, Jing; Liu, Yang; Han, Fangpu; Birchler, James A. (Frontiers in Plant Science, 2015)
The centromere is a specialized chromosomal region identified as the major constriction, upon which the kinetochore complex is formed, ensuring accurate chromosome orientation and segregation during cell division. The rapid evolution of centromere DNA sequence and the conserved centromere function are two contradictory aspects of centromere biology. Indeed, the sole presence of genetic sequence is not sufficient for centromere formation. Various dicentric chromosomes with one inactive centromere have been recognized. It has also been found that de novo centromere formation is common on fragments in which centromeric DNA sequences are lost. Epigenetic factors play important roles in centromeric chromatin assembly and maintenance. Nondisjunction of the supernumerary B chromosome early prophase of meiosis I requires an active centromere. This review discusses recent studies in maize about genetic and epigenetic elements regulating formation and maintenance of centromere chromatin, as well as centromere behavior in meiosis.